Polarization-maintaining anti-radiation erbium-ytterbium co-doped optical fiber and preparation method thereof
By introducing GeO2, Ce2O3 and F components into erbium-ytterbium co-doped optical fiber, optimizing the core NA and mode field diameter, and adopting a polarization-maintaining structure, the problem of optical fiber being easily damaged in high-power communications is solved, and efficient radiation resistance and single-mode transmission are achieved.
Patent Information
- Application Number
- CN202510657698.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-21
- Publication Date
- 2025-09-12
AI Technical Summary
Existing erbium-ytterbium co-doped optical fibers are susceptible to radiation damage in high-power communications, and the increased numerical aperture of the fiber core results in a low fiber laser damage threshold, making it difficult to meet the needs of high-power, large-capacity coherent optical communications.
By optimizing the core doping components and geometric structure design, introducing GeO2, Ce2O3 and F components, reducing the core NA, increasing the mode field diameter, and adopting a polarization-maintaining structure, the optical fiber's radiation resistance and laser damage threshold are improved.
It improves the laser damage threshold and radiation resistance of optical fibers, ensures the single-mode or few-mode transmission characteristics of optical fibers in high-power communications, reduces nonlinear effects, and is suitable for high-power amplifiers in ground and low-orbit satellite communications.
Smart Images

Figure CN120630381A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of active optical fibers, and in particular relates to a polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber and a preparation method thereof. Background Art
[0002] In recent years, the construction of "Star Network" has been a hot topic of development at home and abroad. As early as 2015, the United States Space-X proposed the "Starlink Project" to build satellite Internet, and it has been commercialized in some regions, and European countries are following closely behind.
[0003] Radiation-resistant erbium-ytterbium co-doped fiber is an important gain medium for fiber amplifier devices in satellite communications. Currently, in conventional two-stage amplification fiber amplifiers, the primary optical path uses radiation-resistant erbium-doped fiber, and the secondary optical path uses 10 / 125 single-mode radiation-resistant erbium-ytterbium co-doped fiber. Communication can be achieved with a module output power of less than 5W. Further increasing the pump power and output power will exceed the laser damage threshold of the fiber, easily leading to the risk of fiber burning. Therefore, to meet the needs of future high-power, high-capacity coherent optical communications, it is necessary to develop a large-mode-field polarization-maintaining radiation-resistant erbium-ytterbium co-doped fiber. This will increase the fiber's mode field diameter, thereby improving the fiber's laser damage threshold, while also reducing the fiber's numerical aperture (NA), ensuring the fiber's single-mode or few-mode transmission characteristics and improving beam quality.
[0004] Each component in the doping system of erbium-ytterbium co-doped fiber plays a role. To increase the fiber's pump and output power, the rare earth ion doping concentration needs to be increased, and the amount of P2O5, a "solvent," must also be increased accordingly to prevent clustering. However, this can lead to poor radiation resistance and an increase in the core NA. Therefore, it is crucial to find ways to reduce the core NA and improve the radiation resistance of erbium-ytterbium co-doped fiber. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber, a preform rod and a preparation method thereof. Through the design of geometric structure and doping components, the erbium-ytterbium co-doped optical fiber has a high laser damage threshold and polarization-maintaining performance, while also having good radiation resistance.
[0006] The optical fiber technology solution adopted by the present invention to solve the above-mentioned problems is as follows: it includes an outer cladding layer and a core layer, and stress zones are symmetrically arranged on both sides of the core layer. It is characterized in that the core layer is an erbium-ytterbium co-doped silica glass layer, and the erbium-ytterbium co-doped silica glass layer is based on SiO2 and doped with Er2O3, Yb2O3, P2O5, GeO2, Ce2O3 and F, and the doping amount of each dopant in the core layer is Yb2O3 1.5-2.0mol%, Er2O3 0.1-0.2mol%, P2O5 13.0-15.0mol%, GeO2 5-4.0mol%, F 0.1-1.0mol%, and Ce2O3 0.05-0.3mol%.
[0007] According to the above scheme, the Yb2O3 doping amount in the core layer is 1.5-1.7 mol%, the Er2O3 doping amount is 0.1-0.15 mol%, and the Yb2O3 / Er2O3 ratio is controlled at 8-20.
[0008] According to the above scheme, the P2O5 doping amount in the core layer is 13.0-14.0 mol%, the Ce2O3 doping amount is 0.1-0.25 mol%, and the F doping amount is 0.1-0.5 mol%.
[0009] According to the above solution, the diameter of the core layer is 20-30 μm, and the refractive index difference between the core layer and pure quartz glass is 0.015-0.019.
[0010] According to the above solution, the numerical aperture NA of the optical fiber is 0.07-0.09, and the mode field diameter is 17-25 μm.
[0011] According to the above scheme, the core layer is tightly wrapped with an inner cladding layer, and the inner cladding layer is a germanium, fluorine, and phosphorus co-doped silica glass layer. The germanium, fluorine, and phosphorus co-doped silica glass layer is based on SiO2 and is doped with GeO2, P2O5, and F. The doping amount of each dopant in the core layer is GeO2 8-14 mol%, P2O5 1-4 mol%, and F 0.1-1.0 mol%.
[0012] According to the above solution, the diameter of the inner cladding is 40-45 μm, and the refractive index difference between the inner cladding and pure quartz glass is 0.013-0.015.
[0013] According to the above solution, the diameter of the stress zone is 60 to 90 μm, and the distance between the center of the stress zone and the center of the core layer is 70 to 90 μm.
[0014] According to the above solution, the diameter of the stress zone is 65-75 μm, the distance between the center of the stress zone and the center of the core layer is 75-80 μm, and the relative refractive index difference of the stress zone is ≤-0.008.
[0015] According to the above scheme, the birefringence coefficient of the optical fiber is ≥1.0×10 -4 ; Radiation-induced gain variation ≤0.01dB / krad.
[0016] According to the above scheme, the outer cladding has a diameter of 300±10μm, the outer cladding is a pure silica glass layer, the outer cladding is covered with an inner resin coating layer and an outer resin coating layer, the inner resin coating layer has a diameter of 375±10μm, and the outer resin coating layer has a diameter of 450±20μm.
[0017] The technical solution for preparing the optical fiber of the present invention is:
[0018] Making the core rod: depositing the inner cladding and core layer in the quartz liner in sequence, and then melting the doped deposited liner into a solid core rod after deposition.
[0019] Making a solid preform: inserting a solid core rod into a quartz sleeve, stretching it into a solid preform rod of a certain size through high-temperature melting and shrinkage, and then machining a pair of through holes on both sides of the solid preform rod with the center of the end face as the symmetrical point;
[0020] Making stress rods: doping is done in a quartz liner, and after deposition, the doped and deposited liner is melted and shrunk into a solid stress rod;
[0021] Making a polarization-maintaining optical fiber preform: inserting solid stress rods into the through holes on both sides of the solid preform, and taper one end to make a polarization-maintaining optical fiber preform;
[0022] Drawing polarization-maintaining optical fiber: clamping the polarization-maintaining optical fiber preform rod into a drawing furnace, and drawing the polarization-maintaining optical fiber.
[0023] According to the above scheme, the core rod manufacturing process includes:
[0024] Using the MCVD combined with the chelate evaporation system (CDS) vapor phase process, the reaction raw materials SiCl4, P2O5, GeO2 and F are loaded into a quartz liner tube through oxygen, and the liner tube is heated to 1700-1750℃ to vitrify the raw materials, and the inner cladding is repeatedly deposited on the inner wall of the quartz tube;
[0025] Using a vapor phase process using MCVD combined with a chelate evaporation system (CDS), the raw materials SiCl4, P2O5, GeO2, and F are loaded into a quartz liner using oxygen, and Yb chelate, Er chelate, and Ce chelate are loaded into the quartz liner using helium. The liner is heated to 1500-1600°C to vitrify the raw materials, and a rare earth doped core layer is repeatedly deposited on the inner wall of the quartz tube.
[0026] After the core layer is deposited, the quartz tube is heated to 1800-2100°C, and the surface tension of the glass is used to melt the quartz tube into a doped quartz rod.
[0027] The beneficial effects of the present invention are as follows: 1. By optimizing the core doping components, three components, GeO2, Ce2O3, and F, are introduced into the core to improve the radiation resistance of the optical fiber. GeO2 itself is relatively insensitive to radiation exposure, and the electron and hole defects it produces can interact with and neutralize the radiation-induced defects produced by other components such as P2O5, thereby improving the radiation resistance of the optical fiber and meeting the application requirements of high-power amplifiers in radiation environments such as space. However, the introduction of GeO2 will increase the numerical aperture of the optical fiber core, so the introduction of F is necessary to reduce the core refractive index. F can also combine with SiO2-related defects, replacing O ions in the structure to form stronger Si-F bonds, which also play a role in reducing the generation of SiO2-related radiation-induced defects. 2. The present invention increases the mode field diameter of the optical fiber through the core-cladding structure design, thereby improving the laser damage threshold of the optical fiber and enabling it to withstand higher pump laser power and signal light output power. At the same time, the low numerical aperture design ensures that the signal light maintains the characteristics of single-mode or few-mode transmission in the optical fiber, thereby improving the beam quality. The optical fiber described in this invention has important applications in high-power communication amplifiers for terrestrial and low-orbit satellite communications. The polarization-maintaining structure of the present invention maintains the well-defined polarization mode of the transmitted light within the optical fiber, and the large mode field diameter design reduces the nonlinear effects of high-power pump output. This optical fiber has important applications in high-power, long-distance space communications. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic diagram of the radial structure of an embodiment of the present invention.
[0029] Figure 2 FIG. 1 is a schematic diagram of the structure of an optical fiber preform in one embodiment of the present invention.
[0030] Figure 3 This is a curve diagram of the radiation-induced gain change of the large mode field polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber described in the present invention. DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0032] Examples of embodiments of the optical fiber of the present invention include Figure 1As shown, it includes an outer cladding 4 and a core layer 1, and stress zones 3 are symmetrically arranged on both sides of the core layer. The core layer is an erbium-ytterbium co-doped silica glass layer, which is based on SiO2 and doped with Er2O3, Yb2O3, P2O5, GeO2, Ce2O3 and F. The core layer is tightly wrapped with an inner cladding 2, which is a germanium-fluorine-phosphorus co-doped silica glass layer, which is based on SiO2 and doped with GeO2, P2O5 and F. The diameter of the core layer is 20-30 μm, the diameter of the inner cladding is 40-45 μm, the diameter of the stress zone is 60-90 μm, and the distance between the center of the stress zone and the center of the core layer is 70-90 μm. The outer cladding has a diameter of 300±10 μm, and the outer cladding is coated with an inner resin coating layer 5 and an outer resin coating layer 6. The inner resin coating layer has a diameter of 375±10 μm, and the outer resin coating layer has a diameter of 450±20 μm.
[0033] The present invention is further described below with reference to Examples and Comparative Examples.
[0034] Comparative Example: In this comparative example, the core dopant of the large-mode-field, polarization-maintaining, radiation-hardened Er / Ytterbium co-doped optical fiber comprises P2O5, Er2O3, and Yb2O3, with the doping concentrations of Yb2O3 being 1.5 mol%, Er2O3 being 0.1 mol%, and P2O5 being 13.0 mol%. The inner cladding dopant of the optical fiber comprises P2O5 and GeO2, with the doping concentrations of P2O5 being approximately 2.0 mol%, GeO2 being approximately 13.0 mol%, and the remainder being SiO2.
[0035] The preparation method specifically comprises the following steps:
[0036] S1: Using a vapor-phase process using MCVD combined with a chelate vapor deposition system (CDS), the raw materials SiCl₄, P₂O₅, and GeO₂ are loaded into a quartz tube via oxygen, with carrier gas flows of 300 sccm, 100 sccm, and 500 sccm, respectively. The tube is heated to 1700-1750°C to vitrify the raw materials, and several layers of inner cladding are repeatedly deposited on the inner wall of the quartz tube.
[0037] S2: Using a vapor-phase process using MCVD combined with a chelate evaporation system (CDS), the raw materials SiCl4 and P2O5 are loaded into a quartz liner using oxygen at carrier gas flow rates of 100 sccm and 1000 sccm, respectively. Yb chelate and Er chelate are also loaded into the quartz liner using helium at carrier gas flow rates of 500 sccm and 100 sccm, respectively. The liner is heated to 1500-1600°C to vitrify the raw materials, and several layers of rare earth doped core layers are repeatedly deposited on the inner wall of the quartz tube.
[0038] S3: After the core layer is deposited, the quartz tube is heated to 1800-2100°C, and the surface tension of the glass is used to shrink the quartz tube into a doped quartz rod;
[0039] S4: combining the doped quartz rod and the quartz sleeve into a preform rod by a tube-rod method, and stretching the preform rod into a solid preform rod with a certain outer diameter in a stretching tower;
[0040] S5: processing two through holes in the solid preform at positions symmetrical to the center of the fiber core.
[0041] S6: After cleaning, assembling the two stress rods and the solid preform with the holes processed above into a polarization-maintaining optical fiber preform;
[0042] S7: heating the polarization-maintaining optical fiber preform in a drawing furnace to 1800-2100° C., softening the preform and drawing it into a polarization-maintaining optical fiber.
[0043] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has a fiber cladding diameter of 300 μm, an inner cladding diameter of 43 μm, a refractive index difference between the inner cladding and pure quartz glass of 0.013, a core diameter of 25 μm, a core NA of 0.08, an inner coating diameter of approximately 375 μm, and an outer coating diameter of approximately 450 μm.
[0044] Example 1: In this example, the core dopant in the large mode field polarization-maintaining radiation-hardened erbium-ytterbium co-doped optical fiber includes P2O5, Er2O3, Yb2O3, GeO2, Ce2O3, and F, with the doping concentrations of Yb2O3 being 1.7 mol%, Er2O3 being 0.12 mol%, P2O5 being 14.0 mol%, GeO2 being 2.0 mol%, Ce2O3 being 0.2 mol%, and F being approximately 0.3 mol%. The inner cladding dopant of the optical fiber includes P2O5, GeO2, and F, with the doping concentrations of P2O5 being approximately 4.0 mol%, GeO2 being approximately 13.0 mol%, and F being approximately 0.2 mol%. The remainder of the matrix material is SiO2.
[0045] The preparation method specifically comprises the following steps:
[0046] S1: Using a vapor-phase process using MCVD combined with a chelate vapor deposition system (CDS), the raw materials SiCl₄, P₂O₅, GeO₂, and SiF₄ are loaded into a quartz tube using oxygen. The carrier gas flow rates are 300 sccm, 200 sccm, 500 sccm, and 5 sccm, respectively. The tube is heated to 1700-1750°C to vitrify the raw materials, and several layers of inner cladding are repeatedly deposited on the inner wall of the quartz tube.
[0047] S2: Using a vapor-phase process using MCVD combined with a chelate evaporation system (CDS), the raw materials SiCl4, P2O5, GeO2, and SiF4 are loaded into a quartz liner using oxygen at carrier gas flow rates of 100 sccm, 1200 sccm, 50 sccm, and 7 sccm, respectively. Yb chelate, Er chelate, and Ce chelate are loaded into the quartz liner using helium at carrier gas flow rates of 550 sccm, 150 sccm, and 200 sccm, respectively. The liner is heated to 1500-1600°C to vitrify the raw materials, and several layers of rare earth doped core layers are repeatedly deposited on the inner wall of the quartz tube.
[0048] S3: After the core layer is deposited, the quartz tube is heated to 1800-2100°C, and the surface tension of the glass is used to shrink the quartz tube into a doped quartz rod;
[0049] S4: combining the doped quartz rod and the quartz sleeve into a preform rod by a tube-rod method, and stretching the preform rod into a solid preform rod with a certain outer diameter in a stretching tower;
[0050] S5: Two through holes 7 are processed in the solid preform at positions symmetrical to the center of the fiber core.
[0051] S6: After cleaning, assembling the two stress rods and the solid preform with the holes processed above into a polarization-maintaining optical fiber preform;
[0052] S7: heating the polarization-maintaining optical fiber preform in a drawing furnace to 1800-2100° C., softening the preform and drawing it into a polarization-maintaining optical fiber.
[0053] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has a fiber cladding diameter of 300 μm, an inner cladding diameter of 41 μm, a refractive index difference between the inner cladding and pure quartz glass of 0.0149, a core diameter of 25 μm, a core NA of 0.09, an inner coating diameter of approximately 375 μm, and an outer coating diameter of approximately 450 μm.
[0054] Example 2: In this example, the core dopant in the large mode field polarization-maintaining radiation-hardened erbium-ytterbium co-doped optical fiber includes P2O5, Er2O3, Yb2O3, GeO2, Ce2O3, and F, with the doping concentrations of Yb2O3 being 1.8 mol%, Er2O3 being 0.15 mol%, P2O5 being 15.0 mol%, GeO2 being 3.0 mol%, Ce2O3 being 0.2 mol%, and F being approximately 0.5 mol%. The inner cladding dopant of the optical fiber includes P2O5, GeO2, and F, with the doping concentrations of P2O5 being approximately 4.0 mol%, GeO2 being approximately 13.0 mol%, and F being approximately 0.2 mol%. The remainder of the matrix material is SiO2.
[0055] The preparation method specifically comprises the following steps:
[0056] S1: Using a vapor-phase process using MCVD combined with a chelate vapor deposition system (CDS), the raw materials SiCl₄, P₂O₅, GeO₂, and SiF₄ are loaded into a quartz tube using oxygen. The carrier gas flow rates are 300 sccm, 200 sccm, 500 sccm, and 5 sccm, respectively. The tube is heated to 1700-1750°C to vitrify the raw materials, and several layers of inner cladding are repeatedly deposited on the inner wall of the quartz tube.
[0057] S2: Using a vapor-phase process using MCVD combined with a chelate evaporation system (CDS), the raw materials SiCl4, P2O5, GeO2, and SiF4 are loaded into a quartz liner using oxygen at carrier gas flow rates of 100 sccm, 1500 sccm, 75 sccm, and 10.0 sccm, respectively. Yb chelate, Er chelate, and Ce chelate are loaded into the quartz liner using helium at carrier gas flow rates of 580 sccm, 180 sccm, and 200 sccm, respectively. The liner is heated to 1500-1600°C to vitrify the raw materials, and several layers of rare earth-doped core layers are repeatedly deposited on the inner wall of the quartz tube.
[0058] S3: After the core layer is deposited, the quartz tube is heated to 1800-2100°C, and the surface tension of the glass is used to shrink the quartz tube into a doped quartz rod;
[0059] S4: combining the doped quartz rod and the quartz sleeve into a preform rod by a tube-rod method, and stretching the preform rod into a solid preform rod with a certain outer diameter in a stretching tower;
[0060] S5: processing two through holes in the solid preform at positions symmetrical to the center of the fiber core.
[0061] S6: After cleaning, assembling the two stress rods and the solid preform with the holes processed above into a polarization-maintaining optical fiber preform;
[0062] S7: heating the polarization-maintaining optical fiber preform in a drawing furnace to 1800-2100° C., softening the preform and drawing it into a polarization-maintaining optical fiber.
[0063] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has a fiber cladding diameter of 300 μm, an inner cladding diameter of 45 μm, a refractive index difference between the inner cladding and pure quartz glass of 0.0146, a core diameter of 25 μm, a core NA of 0.07, an inner coating diameter of approximately 375 μm, and an outer coating diameter of approximately 450 μm.
[0064] Example 3: In this example, the core dopants in the large mode field polarization-maintaining radiation-hardened erbium-ytterbium co-doped optical fiber include P2O5, Er2O3, Yb2O3, GeO2, Ce2O3, and F, with the doping concentrations of Yb2O3 being 2.0 mol%, Er2O3 being 0.15 mol%, P2O5 being 15.0 mol%, GeO2 being 4.0 mol%, Ce2O3 being 0.3 mol%, and F being approximately 0.8 mol%. The inner cladding dopants of the optical fiber include P2O5, GeO2, and F, with the doping concentrations of P2O5 being approximately 4.0 mol%, GeO2 being approximately 14.0 mol%, and F being approximately 0.1 mol%. The remainder of the matrix material is SiO2.
[0065] The preparation method specifically comprises the following steps:
[0066] S1: Using a vapor-phase process using MCVD combined with a chelate vaporization system (CDS), the raw materials SiCl₄, P₂O₅, GeO₂, and SiF₄ are loaded into a quartz tube using oxygen. The carrier gas flow rates are 300 sccm, 200 sccm, 600 sccm, and 3 sccm, respectively. The tube is heated to 1700-1750°C to vitrify the raw materials, and several layers of inner cladding are repeatedly deposited on the inner wall of the quartz tube.
[0067] S2: Using a vapor-phase process using MCVD combined with a chelate evaporation system (CDS), the raw materials SiCl4, P2O5, GeO2, and SiF4 are loaded into a quartz liner using oxygen at carrier gas flow rates of 100 sccm, 1500 sccm, 90 sccm, and 14.0 sccm, respectively. Yb chelate, Er chelate, and Ce chelate are loaded into the quartz liner using helium at carrier gas flow rates of 600 sccm, 200 sccm, and 250 sccm, respectively. The liner is heated to 1500-1600°C to vitrify the raw materials, and several layers of rare earth-doped core layers are repeatedly deposited on the inner wall of the quartz tube.
[0068] S3: After the core layer is deposited, the quartz tube is heated to 1800-2100°C, and the surface tension of the glass is used to shrink the quartz tube into a doped quartz rod;
[0069] S4: combining the doped quartz rod and the quartz sleeve into a preform rod by a tube-rod method, and stretching the preform rod into a solid preform rod with a certain outer diameter in a stretching tower;
[0070] S5: processing two through holes in the solid preform at positions symmetrical to the center of the fiber core.
[0071] S6: After cleaning, assembling the two stress rods and the solid preform with the holes processed above into a polarization-maintaining optical fiber preform;
[0072] S7: heating the polarization-maintaining optical fiber preform in a drawing furnace to 1800-2100° C., softening the preform and drawing it into a polarization-maintaining optical fiber.
[0073] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has a fiber cladding diameter of 300 μm, an inner cladding diameter of 42 μm, a refractive index difference between the inner cladding and pure quartz glass of 0.014, a core diameter of 25 μm, a core NA of 0.08, an inner coating diameter of approximately 375 μm, and an outer coating diameter of approximately 450 μm.
[0074] For the large mode field polarization maintaining radiation-resistant erbium-ytterbium co-doped optical fiber in the comparative example and specific embodiments 1 to 3, the doping substances and radiation-induced gain changes at different locations are summarized as follows:
[0075]
[0076] The test results of radiation-induced gain changes in the examples and comparative examples show that the fiber doping components provided by the present invention can significantly improve the radiation resistance of the optical fiber. Furthermore, as the GeO2, Ce2O3, and F content in the core layer increases, the radiation resistance of the optical fiber also improves. The large-mode-field, polarization-maintaining, radiation-resistant erbium-ytterbium co-doped optical fiber of the present invention improves its radiation resistance and laser damage threshold by optimizing the fiber geometry and doping design. This ensures that gain media such as erbium-ytterbium co-doped optical fiber exhibit excellent optical amplification performance in radiation-rich environments such as space, and thus has important application value in high-power amplifier modules for space communications and integrated space-ground optical communications.
[0077] It will be easily understood by those skilled in the art that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber, comprising an outer cladding layer and a core layer, wherein stress zones are symmetrically arranged on both sides of the core layer, characterized in that The core layer is an erbium-ytterbium co-doped silica glass layer, which takes SiO2 as a matrix and is doped with Er2O3, Yb2O3, P2O5, GeO2, Ce2O3 and F. The doping amount of each dopant in the core layer is Yb2O3 1.5-2.0 mol%, Er2O3 0.1-0.2 mol%, P2O5 13.0-15.0 mol%, GeO2 5-4.0 mol%, F 0.1-1.0 mol%, and Ce2O3 0.05-0.3 mol%.
2. The polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber according to claim 1, characterized in that The doping amount of P2O5 in the core layer is 13.0-14.0 mol%, the doping amount of Ce2O3 is 0.1-0.25 mol%, and the doping amount of F is 0.1-0.5 mol%.
3. The polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber according to claim 1 or 2, characterized in that The diameter of the core layer is 20-30 μm, and the refractive index difference between the core layer and pure quartz glass is 0.015-0.
019.
4. The polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber according to claim 3, characterized in that The numerical aperture NA of the optical fiber is 0.07-0.09, and the mode field diameter is 17-25 μm.
5. The polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber according to claim 1 or 2, characterized in that The core layer is tightly wrapped with an inner cladding layer, which is a germanium, fluorine and phosphorus co-doped silica glass layer. The germanium, fluorine and phosphorus co-doped silica glass layer is based on SiO2 and is doped with GeO2, P2O5 and F. The doping amount of each dopant in the core layer is GeO2 8-14mol%, P2O5 1-4mol%, and F 0.1-1.0mol%.
6. The polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber according to claim 5, characterized in that The inner cladding has a diameter of 40 to 45 μm, and the refractive index difference between the inner cladding and pure quartz glass is 0.013 to 0.
015.
7. The polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber according to claim 1 or 2, characterized in that The diameter of the stress zone is 60-90 μm, the distance between the center of the stress zone and the center of the core layer is 70-90 μm, and the refractive index difference between the stress zone and the pure quartz glass is ≤-0.
008.
8. The polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber according to claim 7, characterized in that The diameter of the stress zone is 65-75 μm, and the distance between the center of the stress zone and the center of the core layer is 75-80 μm.
9. The polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber according to claim 1 or 2, characterized in that The birefringence index of the optical fiber is ≥1.0×10 -4 ; Radiation-induced gain variation ≤0.01dB / krad.
10. The polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber according to claim 1 or 2, characterized in that The outer cladding has a diameter of 300±10 μm, and the outer cladding is coated with an inner resin coating layer and an outer resin coating layer. The inner resin coating layer has a diameter of 375±10 μm, and the outer resin coating layer has a diameter of 450±20 μm.
11. A method for preparing a polarization-maintaining, radiation-resistant erbium-ytterbium co-doped optical fiber, for preparing the polarization-maintaining, radiation-resistant erbium-ytterbium co-doped optical fiber according to any one of claims 1 to 10, characterized in that Making the core rod: depositing the inner cladding and core layer in the quartz liner in sequence, and then melting and shrinking the doped deposited liner into a solid core rod after deposition; Making a solid preform: inserting a solid core rod into a quartz sleeve, stretching it into a solid preform rod of a certain size through high-temperature melting and shrinkage, and then machining a pair of through holes on both sides of the solid preform rod with the center of the end face as the symmetrical point; Making stress rods: doping is done in a quartz liner, and after deposition, the doped and deposited liner is melted and shrunk into a solid stress rod; Making a polarization-maintaining optical fiber preform: inserting solid stress rods into the through holes on both sides of the solid preform, and taper one end to make a polarization-maintaining optical fiber preform; Drawing polarization-maintaining optical fiber: clamping the polarization-maintaining optical fiber preform rod into a drawing furnace, and drawing the polarization-maintaining optical fiber.
12. The method for preparing polarization-maintaining radiation-resistant erbium-ytterbium co-doped optical fiber according to claim 11, characterized in that The core rod manufacturing process includes Using the vapor phase process of MCVD combined with the chelate evaporation system CDS, the reaction raw materials SiCl4, P2O5, GeO2 and F are loaded into a quartz liner tube through oxygen, and the liner tube is heated to 1700-1750℃ to vitrify the raw materials, and the inner cladding is repeatedly deposited on the inner wall of the quartz tube; Using the vapor phase process of MCVD combined with the chelate evaporation system CDS, the reaction raw materials SiCl4, P2O5, GeO2 and F are loaded into a quartz liner by oxygen, and Yb chelate, Er chelate and Ce chelate are loaded into the quartz liner by helium. The liner is heated to 1500-1600℃ to vitrify the raw materials, and a rare earth doped core layer is repeatedly deposited on the inner wall of the quartz tube. After the core layer is deposited, the quartz tube is heated to 1800-2100°C, and the surface tension of the glass is used to melt the quartz tube into a doped quartz rod.
Citation Information
Patent Citations
Multi-mode erbium-ytterbium co-doped optical fiber, core rod and preparation method and application thereof
CN115818950A
Boron-germanium co-doped polarization-maintaining photosensitive optical fiber and preparation method thereof
CN117369041A
Anti-radiation erbium-ytterbium co-doped optical fiber core rod, preform, optical fiber and preparation method thereof
CN119241082A
Fiber optic article with inner region
US20060029343A1
Process of fabrication of erbium and ytterbium-co-doped multi-elements silica glass based cladding-pumped fiber
US20190375672A1